Assessment on reproductive performance of crossbred dairy cows selected as recipient for embryo transfer in urban set up bishoftu, Central Ethiopia - Yonas Getachew; Alemayehu Lemma; Haben Fesseha (International Journal of Veterinary Science and Research - Peertechz Publications, 2020)
The reproductive status of a recipient cow is among the factors that influence the success of embryo transfer in bovine. The study was carried out on a total of 276 cows from 25 dairy farms classified as large (>20 cows), medium (10-20 cows) and small scale (1-10 cows) dairy production system. Data were collected through personal interviews of owners, from an individual animal record and gynecological evaluation of animals. Accordingly, the overall mean (±SD) of AFC, CI, LL, DMY, and NSPC were 30.07±2.17 months, 13.33±2.84 months, 9.08±1.10 months, 14.33±4.59 liters/day and 1.59±1.02, respectively. Milk yield and body condition did not have a significant effect on NSPC (P > 0.05) whereas parity significantly influenced NSPC, with cows in parity 3 showing the lowest NSPC (p<0.05). Farm size significantly influenced AFC, NSPC, and DMY (p<0.05). Milk yield was highly associated with increasing parity number. There was no statistically significant difference in NSPC between the breeding method (AI and NS) (P > 0.05). In conclusion, most of the reproductive parameters of the present population were within the range, however, some of the reproductive indices tended to be influenced by the scale of production. Findings of this study highlight that the selection of embryo recipient cows in the small and medium-sized farms should be meticulous considering the important indices particularly NSPC. Besides, feeding management, as shown by the body condition has been another parameter requiring consideration, particularly in small scale production.